Forecasting stock market averages to enhance profitable trading strategies - Christian Haefke; Christian Helmenstein (Institute for Advanced Studies (IHS), 1995)
In this paper we design a simple trading strategy to exploit the hypothesized distinct informational content of the arithmetic and geometric mean. The rejection of cointegration between the two stock market indicators supports this conjecture. The profits generated by this cheaply replicable trading scheme cannot be expected to persist. Therefore we forecast the averages using autoregressive linear and neural network models to gain a competitive advantage relative to other investors. Refining the trading scheme using the forecasts further increases the mean return as compared to a buy and hold strategy. – – In der vorliegenden Arbeit formulieren wir ein einfaches Trading System, um den unterschiedlichen Informationsgehalt des arithmetischen und geometrischen Mittels auszuschöpfen. Kointegrationstests verwerfen die Existenz einer langfristigen Gleichgewichtsbeziehung zwischen den beiden Aktienindizes. Da dieses Handelssystem leicht replizierbar ist, kann eine Persistenz dieser Profite nicht erwartet werden. Aus diesem Grunde prognostizieren wir beide Kursdurchschnitte mit autoregressiven linearen und neuronalen Netzwerk Modellen, um gegenüber anderen Investoren einen kompetitiven Vorteil zu erlangen. Im Vergleich zu einer Buy and Hold Strategie erhöht diese Verbesserung des Handelssystems den durchschnittlichen Ertrag.
Keywords: G14; C43; C45; C53; 330; trading strategy; stock market index; neural networks; cointegration; Börsenkurs; Aktienindex; Neuronale Netze; Prognoseverfahren; Theorie